Exploration of the Structure and Composition of Sn(S₀.₆Te₀.₄) Thin Film as a Potential Absorber in Solar Cell Technology - Setianingrum, Mahmudah; Bozorboeva, Guluzra (Journal of Chemical Learning Innovation, 2024)
Purpose of the study: This study aims to synthesize and characterize Sn(S₀.₆Te₀.₄) thin films using vacuum evaporation and to analyze their crystal structure and chemical composition in order to evaluate their potential as absorber materials for solar cell applications. Methodology: Vacuum evaporation system with rotary and diffusion pumps, substrate heater, Penning manometer, thermocouple, furnace, digital balance, and multimeter were used. Structural analysis employed X-Ray Diffraction (Miniflex 600 Rigaku, Cu source). Surface morphology and composition were analyzed using Scanning Electron Microscopy (SEM) and Energy Dispersive Spectroscopy (EDS). Data processed using Origin and PCPDFWIN software. Main Findings: Sn(S₀.₆Te₀.₄) thin films were successfully deposited at 250°C, 300°C, and 350°C. XRD results show increased diffraction peak intensity with higher temperature, indicating improved crystallinity, with optimum at 350°C. The structure approaches orthorhombic SnS. EDS confirms presence of Sn, S, and Te with composition close to theoretical values but slightly deviated due to non-stoichiometric effects. Novelty/Originality of this study: This study explores a specific composition of Sn(S₀.₆Te₀.₄) thin film using vacuum evaporation and simultaneously analyzes its crystal structure and chemical composition. It provides new insight into the relationship between temperature, crystallinity, and composition, contributing to the development of alternative absorber materials for solar cell technology.